APPROACHES AND CHALLENGES IN LITERARY TRANSLATION - Abdullayeva Zarina Shukhrat kizi (Scholar Express Journal, 2024)
Translators often face the dilemma of whether to prioritize literal accuracy or creative adaptation. While literal translations ensure fidelity to the original, creative translations allow for the recreation of cultural nuances and poetic elements. A balanced approach that takes into account the context and purpose of the translation is often employed. In this article mentioned about approaches and challenges in literary translation.
Keywords: Literary translation; lyrics; rhythm; idiomatic phrases